INNOVATION IN LOCAL WISDOM-BASED LEARNING: DEVELOPING TEACHING MATERIALS ON JAMBI MALAY CULTURE IN PRIMARY SCHOOLS - Tio Tanra Azaria; Yantoro Yantoro; Atri Widowati (El Midad, 2025)
This study was motivated by the lack of contextual learning materials that integrate local cultural values into elementary education, particularly related to Jambi Malay Culture. The absence of appropriate teaching resources has resulted in limited student understanding of local wisdom and cultural identity. Therefore, this study aims to develop innovative local content teaching materials based on Jambi Malay Culture to strengthen students’ character and appreciation of their cultural heritage. The research employed a Research and Development (R&D) method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants of this study were fourth-grade students at SD Negeri 151/IV Jambi City. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning achievement tests. The results of the study show that (1) the validity of the developed teaching materials was categorized as very valid with an average score of 3.68 out of 4, covering content accuracy, language, and visual design; (2) the practicality was very practical with a score of 85%, as both teachers and students responded positively to ease of use and attractiveness; and (3) the effectiveness was proven by a 27% increase in students’ posttest results, indicating improved understanding of local cultural values